Impact of aortic valve calcification on the outcome of transcatheter aortic valve implantation: Results from the prospective multicenter German TAVI registry. Issue 2 (4th May 2012) - Staubach, Stephan; Franke, Jennifer; Gerckens, Ulrich; Schuler, Gerhard; Zahn, Ralf; Eggebrecht, Holger; Hambrecht, Rainer; Sack, Stefan; Richardt, Gert; Horack, Martin; Senges, Jochen; Steinberg, Daniel H.; et al.
<x xml:space="preserve">Abstract</x> Objectives Transcatheter aortic valve implantation (TAVI) is an emerging technology in patients with severe aortic stenosis. Background Whether the degree of aortic valve calcification impacts the outcome after TAVI has not been thoroughly evaluated. Methods We analyzed data from the prospective multicenter German TAVI registry, including 1, 365 patients as of July 2010. Patients were divided into three groups, based on the degree of aortic valve calcification: mild (n = 67), moderate (n = 392), and severe (n = 906) valve calcification, determined by visual estimation by the operator. Results Mean age was 81.7 ± 6.2 years; mean logistic EUROscore was 20.6 ± 13.7%. Patients with severe aortic valve calcification had a higher mean and peak‐to‐peak gradient before the intervention (P < 0.0001). Technical success was achieved in 97%, similar in each group. The Medtronic CoreValve was implanted in 80.8%, the Sapien Edwards prosthesis in the remaining cases. The duration of the procedure and fluoroscopy was higher in the group with severe calcification (P < 0.01 for procedure and P < 0.05 for fluoroscopy). During the periprocedural period there were no differences among the groups regarding in‐hospital death, cerebrovascular events, myocardial infarction, thromboembolic events, aortic dissection, or severe vascular complications. Furthermore, there was no significant difference in postprocedural aortic mean gradient (7.0 mm Hg vs. 5.6 mm Hg vs. 6.3 mm Hg; P = 0.07), in residual aortic regurgitation (74% vs. 72% vs. 68%; P = 0.3) or postprocedure pacemaker implantation (38% vs. 30.4% vs. 34.2%; P = 0.35). During 30‐day follow up there was no difference in regard to the number of death, strokes, and myocardial infarctions. Conclusions Our results of a real‐world registry suggest that the extent of aortic valve calcification does not influence the success or procedural outcome significantly. © 2012 Wiley Periodicals, Inc.